The Salvation of Israel Jews in Christian Eschatology from Paul to the Puritans - Cohen, Jeremy (Cornell University Press, 2022)
The Salvation of Israel investigates Christianity's eschatological Jew, the role and characteristics of the Jews at the end of days in the Christian imagination. It explores the depth of Christian ambivalence regarding these Jews, from Paul's Epistle to the Romans, through late antiquity and the Middle Ages, to the Puritans of the seventeenth century. Jeremy Cohen contends that few aspects of a religion shed as much light on the character and the self-understanding of its adherents as its expectations for the end of time. Moreover, eschatological beliefs express and mold an outlook toward non-believers, situating them in an overall scheme of human history and conditioning interaction with them as that history unfolds.Cohen's close readings of biblical commentary, theological texts, and Christian iconography reveal the dual role of the Jews of the last days. For rejecting belief and salvation in Jesus Christ, they have been linked to the false messiah, the Antichrist, the agent of Satan and the exemplary embodiment of evil. Yet from its inception, Christianity has also hinged its hopes for the Second Coming on the enlightenment and repentance of the Jews; for then, as Paul prophesized, "all Israel will be saved."In its vast historical scope, from the ancient Mediterranean world of early Christianity to seventeenth century England and New England, The Salvation of Israel offers a nuanced and insightful assessment of Christian attitudes toward Jews, rife with inconsistency and complexity, thus contributing significantly to our understanding of Jewish-Christian relations
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2022)
Keywords: Jewish Studies; Medieval & Renaissance Studies; Religious Studies; RELIGION / Judaism / General; Antichrist -- History of doctrines; Christianity and other religions -- Judaism; End of the world -- History of doctrines; Judaism (Christian theology) -- History of doctrines; Judaism -- Relations -- Christianity